Analisis Terhadap Putusan Mahkamah Konstitusi Republik Indonesia Nomor 60/PUU-XXII/2024 Tentang Ambang Batas Pencalonan Kepala Daerah di Pilkada Tahun 2024 Menimbulkan Ketidakpastian Hukum Untuk Pilkada Berikutnya - Sihaloho, Hasiholan (Jurusan Hukum Fakultas Dharma Duta Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
In response to the legal uncertainty arising from Constitutional Court Decision No. 60/PUU-XXII/2024 regarding the candidacy threshold for regional head elections (Pilkada), several strategic recommendations can be implemented to ensure a more transparent and fair electoral process. These include: (a) establishing clear procedural policies, (b) strengthening the role of the legislature (DPR) in lawmaking, (c) limiting the authority of the Constitutional Court, (d) promoting legal education and public awareness, (e) monitoring and evaluating the election process, and (f) conducting academic studies and research. In the context of the regional head candidacy threshold, regulations regarding this threshold should no longer be subject to change within 200 days before the opening of candidate registration by the General Election Commission (KPU). If this measure is not enforced, referring to Constitutional Court Decision No. 60/PUU-XXII/2024, which was issued seven days before the KPU accepted candidate registrations, the Constitutional Court could potentially amend the candidacy threshold regulations just one day before the KPU begins accepting candidate registrations in the 2029 Pilkada.